2016
DOI: 10.1371/journal.pone.0167144
|View full text |Cite
|
Sign up to set email alerts
|

Field Trial of an Aerially-Distributed Tuberculosis Vaccine in a Low-Density Wildlife Population of Brushtail Possums (Trichosurus vulpecula)

Abstract: Oral-delivery Mycobacterium bovis bacillus Calmette-Guérin (BCG) vaccine in a lipid matrix has been shown to confer protection against M. bovis infection and reduce the severity of tuberculosis (TB) when fed to brushtail possums (Trichosurus vulpecula), the major wildlife vector of bovine TB in New Zealand. Here we demonstrate the feasibility of aerial delivery of this live vaccine in bait form to an M. bovis-infected wild possum population, and subsequently assess vaccine uptake and field efficacy. Pre-trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Complement component C3 was identified as naturally associated with TB vaccine protection in wild boar [36], red deer [17,98] and zebrafish (Danio rerio) [39,125]. Different studies in domestic animals and wildlife have also shown how BCG induced an innate trained immune response by aerosol, oral or parenteral route [18,75,121,126]. This was also observed in goats vaccinated intranasally and subcutaneously with SO 2 and MTBVAC, respectively [48,87].…”
Section: Immune Responsementioning
confidence: 96%
See 2 more Smart Citations
“…Complement component C3 was identified as naturally associated with TB vaccine protection in wild boar [36], red deer [17,98] and zebrafish (Danio rerio) [39,125]. Different studies in domestic animals and wildlife have also shown how BCG induced an innate trained immune response by aerosol, oral or parenteral route [18,75,121,126]. This was also observed in goats vaccinated intranasally and subcutaneously with SO 2 and MTBVAC, respectively [48,87].…”
Section: Immune Responsementioning
confidence: 96%
“…Detailed lesion scoring (macroscopic and microscopic) is a common practice to determine the degree of vaccine-induced protection in laboratory trials [15,18,23,26,27,36,39,75,89]. Total lesion prevalence was used to determine vaccine efficacy in field trials in cattle and wildlife TB studies [8,14,38,53,[119][120][121]. The studies with BCG and HIMB (parenteral/oral) reduced the total disease burden, especially the thoracic lesions in goats, deer, wild boar and badgers experimentally challenged with M. bovis [17,18,36,48,89,91] or in field studies [14,38,65].…”
Section: Pathology and Microbiologic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cattle vaccination with attenuated M. bovis BCG can negatively interfere with the intradermal tuberculin test applied by routine for diagnosis, so it is forbidden in several countries, including the European Union (EU) member states. However, several experimental trials are currently being conducted in wildlife hosts, such as badger (Aznar et al, 2018; Gormley et al, 2017) and wild boar (Díez‐Delgado et al, 2018; Garrido et al, 2011) in Europe or brushtail possum (Nugent et al, 2016) in New Zealand. The specific characteristics of the vaccine ( M. bovis BCG or heat‐inactivated M. bovis ; with or without adjuvants); the administration method (oral, parenteral); the characteristics of oral baits; and, in field trials, the unknown immune condition of the host undergoing vaccination together with the number of times the same individual could be in contact with the vaccine all contribute to shaping the (variable) immune response (Aznar et al, 2018; Chambers et al, 2017; Díez‐Delgado et al, 2018; Gormley et al, 2017; Nugent et al, 2016).…”
Section: Drivers Of Animal Tb Heterogeneitymentioning
confidence: 99%
“…More convincingly, intra-gastric administration of BCG to brush-tailed possums (the principal wildlife reservoir of TB in New Zealand) was less effective than vaccine administered by the same route in combination with a drug to reduce gastric acidity or when administered intra-duodenally [12,13]. Protection of BCG against degradation in the gut is also the basis of efforts to formulate BCG in a lipid matrix for oral delivery to wildlife [14][15][16].…”
Section: Introductionmentioning
confidence: 99%